2021
DOI: 10.1002/brb3.2045
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life among Ethiopian pregnant women during COVID‐19 pandemic

Abstract: Objective To explore the quality of life and its association with perceived social support and pandemic fear among pregnant women. Methods Cross‐sectional study was conducted among 384 pregnant mothers at southwest Ethiopia from August 1, 2020, to August 15, 2020. Participants were included by consecutive sampling. Quality of life was assessed by short version of WHO quality of life. Social support and fear of COVID‐19 were evaluated by Multidimensional Scale of Perceived Social Support (MSPSS) and fear of COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…More details about the demographic characteristics of the study participants were explained in our previous paper. 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More details about the demographic characteristics of the study participants were explained in our previous paper. 27 …”
Section: Resultsmentioning
confidence: 99%
“…The current study was part of a previously published project 27 and the details of the methodologies were elaborated there.…”
Section: Methodsmentioning
confidence: 99%
“…20,21 Although, studies revealed that strong social support during pregnancy has a positive impact to improving maternal quality of life (QOL) and preventing the adverse pregnancy outcomes, 22 COVID-19 related fear has a negatively effects QOL. 23 Due to COVID-19 preventive measures recommendation, the likelihood of developing anxiety and depressive symptoms are increased among pregnant women who are mainly due to poor social support even within family members. 24 Although the Ethiopian government is highly dedicated to controlling the outbreak after the first case of COVID-19 on March 13, 2020, 25 the incidence of the virus is continuously accelerating every day.…”
Section: Introductionmentioning
confidence: 99%
“…This questionnaire has been developed by Ahorsu et al (2020) and its validity and reliability in Iran have been investigated in several psychometric studies, where it has been confirmed by item-total correlation test and panel assessment. Other relevant characteristics of this questionnaire have also been verified by both classical test theory and Rasch model on a seven-item scale with a Cronbach's alpha of 0.82 (38). In this study, Cronbach's alpha of this questionnaire was also measured.…”
Section: Part I -Personal Informationmentioning
confidence: 54%